Effects of Rolapitant Administered Intravenously or Orally on the Pharmacokinetics of Digoxin (P‐glycoprotein Substrate) and Sulfasalazine (Breast Cancer Resistance Protein Substrate) in Healthy Volunteers. (14th September 2017) - Wang, Xiaodong; Zhang, Zhi‐Yi; Arora, Sujata; Hughes, Lorraine; Wang, Jing; Powers, Daniel; Christensen, Jennifer; Lu, Sharon; Kansra, Vikram
Abstract: Rolapitant is a selective and long‐acting neurokinin‐1 receptor antagonist approved in an oral formulation in combination with other antiemetic agents for the prevention of delayed chemotherapy‐induced nausea and vomiting in adults. Four open‐label phase 1 studies evaluated the safety and drug–drug interactions of a single dose of rolapitant given intravenously (166.5 mg) or orally (180 mg) with oral digoxin (0.5 mg) or sulfasalazine (500 mg), probe substrates for the P‐glycoprotein (P‐gp) and breast cancer resistance protein (BCRP), respectively. Administration of intravenous rolapitant with the substrates did not result in clinically significant effects on digoxin and sulfasalazine pharmacokinetics. In contrast, peak concentration and area under the curve for last quantifiable plasma concentrations increased by 71% (geometric mean ratio [GMR], 1.71; 90% confidence interval [CI], 1.49–1.95) and 30% (GMR, 1.30; 90%CI, 1.19–1.42), respectively, when rolapitant was coadministered orally with digoxin compared with digoxin alone; they increased by 140% (GMR, 2.40; 90%CI, 2.02–2.86) and 127% (GMR, 2.27; 90%CI, 1.94–2.65), respectively, when rolapitant was given orally with sulfasalazine compared with sulfasalazine alone. Adverse events were mild to moderate in severity in the absence or presence of rolapitant. There were no abnormal clinical laboratory or electrocardiogram findings. Thus, whether administered orally or intravenously, rolapitant was safe and well tolerated. Patients taking oral rolapitant with P‐gp and BCRP substrates with a narrow therapeutic index should be monitored for potential adverse events; although increased plasma concentrations of these substrates may raise the risk of toxicity, they are not contraindicated.